Silenced Knowing: An Intersectional Framework for Exploring Black Women's Health and Diasporic Identities - Serrant, Laura (Frontiers in Sociology, 2020)
Understanding the needs of Black women within a cultural and medical framework which recognises the impact on health and wellbeing on the spaces where culture, health and expectation intersect remains a challenge. In the UK, Black women are often more likely to have poor prognosis, worse outcomes and greater morbidity from treatable and preventable health conditions than their white peers. UK researchers have struggled to find a culturally appropriate safe methodological framework to help explore the challenges faced by Black women and their families in safeguarding their health, particularly around sensitive issues such as sexual and reproductive health. This article presents a relatively new intersectional framework using examples of health research on culturally sensitive health issues. The Silences Framework introduces the notion of ‘Screaming Silences’. Screaming Silences (or Silences) reflect the unsaid or unshared aspects of how beliefs, values and experiences of (or about) some groups affect their health and life chances. The article will explore how, the framework aligns with existing intersectional approaches and illustrates how it could be used to expose intersectional nature of issues which influence and inform both individual and group understandings Black Women's health using examples relating to sexual health and life chances for Black women in the Diaspora